Demokrat Parti Erken Dönemi Din-Siyaset İlişkisi - Türköz, Elif Nagihan (Muş Alparslan Üniversitesi, 2021)
Din-siyaset ilişkisi sosyal bilim alanında güncelliğini koruyan araştırma konulardan biri olagelmiştir. Türkiye’nin siyasal hayatında bir dönüm noktası kabul edilen Demokrat Parti erken döneminde yaşanan gelişmelerin aydınlatılması ise din-siyaset ilişkisi anlamında ayrı bir öneme sahiptir. Bu dönemde, çok partili hayata geçişin yanı sıra dini alanda gerçekleştirilen bazı açılımlar söz konusudur. Bu açılımlar neticesinde Türkiye’nin siyasi hayatına damgasını vuran merkez-çevre ayrımı belirginleşmiş ve günümüzde halen devam eden din-siyaset ilişkisinin temel sorunsalları şekillenmeye başlamıştır. Çalışma bu temel sorunsallara ışık tutmak amacıyla DP erken dönemi din-siyaset ilişkisini ele almaktadır. Din siyaset ilişkisi ele alınırken, bu ilişkinin ana omurgasını laiklik tartışmalarının oluşturduğu vurgulanmıştır. DP laiklik ilkesine bağlılığını sürekli bir biçimde vurgulama ihtiyacı hissetmiştir. Bu durum çalışmada, Tek Parti döneminden miras alınan toplumsal ve siyasal hafızanın etkisi ile açıklanmıştır. Demokrat parti din-siyaset ilişkisi geçmiş dönemin mirası açısından da ele alınmıştır. Demokrat Parti döneminin bazı noktalarda geçmişin mirası temelinde siyasetini şekillendirmiştir. Bu mirası çok yönlü miras olarak temellendirebiliriz. Çok yönlü mirasın ilk boyutu, merkez-çevre dikotomisine de referans yaparak açıklanmıştır. Diğer bir deyişle; bu boyutun halkın DP iktidarından talepleri doğrultusunda şekillendiğini ifade edebiliriz. Çalışmada bu boyut, “dini talep mirası” olarak adlandırılmıştır. İkinci boyut çalışmada “laiklik mirası” olarak adlandırılmıştır. Son boyut çalışmada “Milli din mirası” olarak açıklanır.

The relationship between religion and politics has been one of the actual research topics in the field of social science. The early Democrat Party period developments are considered as a turning point in Turkey’s political life. The clarification of this period has a special importance in terms of the relationship between religion and politics. In this period, there are some developments in the religious field besides the transition to multi-party life. As a result of these developments the center-periphery distinction which stamps to Turkey’s political life has become evident and the main problems of the religion-politics relationship that still is ongoing today began to take shape. In order to shed light on these basic problems, this study deals with the relationship between religion and politics in early DP period. While dealing with the religion-politics relationship, it was emphasized that the main backbone of this relationship was the discussions of secularism. DP has consistently emphasized its commitment to secularism. This situation was explained in the study by the effect of social and political memory inherited from the Single Party period. The relationship between religion and politics in the democratic party period is discussed in terms of the legacy of the past period. The Democrat Party shaped its politics at some points on the basis of the legacy of the past. We can base this legacy as a multi-faceted legacy. The first dimension of the multifaceted legacy is explained with reference to the center-periphery dichotomy. In an other words; We can say that this dimension is shaped in line with the demands of the people from the DP government. In the study, this dimension has been named as "the legacy of religious demand". The second dimension is named as "the legacy of secularism" in the study. The last dimension is explained as "National religion legacy" in the study.
Relationship Between Religion and Politics in the Early Period of the Democrat Party
anemon
Keywords: DP; Laiklik; Din-Siyaset İlişkisi; Toplumsal Hafıza; DP; Laicism; Relationship of Religion-Politics; Social Memory